Development of A novel ferroptosis-related prognostic signature with multiple significance in paediatric neuroblastoma - Wang, Xin; Yang, Jun; Bian, Hongqiang; Yang, Hu (Frontiers in Pediatrics, 2023)
Background: Ferroptosis is an iron-dependent regulated cell death pathway that plays an essential role in the occurrence and development of tumours. Nonetheless, little is known about the impact of ferroptosis-related genes (FRGs) on neuroblastoma. Methods: Transcriptional profiles and clinicopathological data of neuroblastoma were downloaded from the TARGET and GEO datasets. These were used as the training set and the validation set, respectively. Non-negative matrix factorisation was employed to divide patients with neuroblastoma into distinct ferroptosis clusters. The Cox regression model with LASSO was performed based on the FRGs to construct a multigene signature, which was subsequently evaluated in the testing set. Finally, we analysed the differences in the tumour immune microenvironment (TIME) and immunotherapeutic response among the different risk groups. Results: The two distinct ferroptosis subtypes were determined and correlated with different clinical outcomes and tumour-infiltrating immune cells (TIICs). A risk model was developed to explore the risk scores of the individual patients. Patients in the low-risk group survived significantly longer than those in the high-risk group and showed a good predictive performance in the testing set. The risk score was significantly linked to clinicopathological traits, and it was confirmed as an independent prognostic indicator for assessing the overall survival. We also found that patients with low-risk scores had a higher infiltration of TIICs and a better immunotherapeutic response. Conclusions: This study showed the potential role of FRGs in contributing to the clinical features, prognosis, TIME, and immunotherapy of neuroblastoma cases. Our findings offer a valuable basis for future research in targeting ferroptosis and its TIME and provide novel measures for the prevention and treatment of neuroblastoma.